The Effectiveness of Learning to Write Poetry with Think Talk Write (TTW) Model - Lysa Amorita Rachmawati; Teguh Supriyanto; Mukh Doyin (Universitas Negeri Semarang, 2022)
Many problems in learning activities to write poetry trigger the low ability to write poetry for fifth grade students at State Elementary Schools in Kedungjati District. Some of the problems experienced by students in learning to write poetry include: motivation, unattractive teacher explanations, difficulty expressing ideas, and the most basic problem for students is the learning model which tends to be monotonous. An effective learning model is one of the important factors for teachers or students in improving students' ability to write poetry. Cooperative learning model is one of the learning models that can improve students' writing skills. Think Talk Write (TTW) learning model is one of the learning models in cooperative learning that can make students able to communicate and express their thoughts to their friends so that they can exchange ideas in writing. . The purpose of this study was to determine the effectiveness of learning to write poetry with the TTW model. This research is using experimental method. The subjects of this study were fifth grade elementary school students in Kedungjati District for the 2017/2018 academic year. Data collection uses tests and non-tests. The data analysis technique used the t test with the help of the SPSS program. The results of learning to write poetry between before and after being given learning to write poetry with the TTW model with the acquisition of t count = 12,293 with sig < 0.05. The results of this study indicate that the TTW learning model can improve students' poetry writing skills.